Uji efektivitas Antibakteri Ekstrak Kulit Pisang Kepok (Musa parasidiaca L.) Terhadap Bakteri Staphylococcus dan Salmonella typhi - Benny Hartono (Program Studi Farmasi UNAJA, 2025)
This study aims to evaluate the antibacterial effectiveness of kepok banana (Musa paradisiaca L.) peel extract against Staphylococcus aureus and Salmonella typhi. The research was conducted at the laboratory of Universitas Adiwangsa Jambi. The banana peel extract was obtained through maceration using 96% ethanol as a solvent. Antibacterial activity was tested using the disc diffusion method against both bacterial strains. The results showed that the extract exhibited significant antibacterial activity, as indicated by the inhibition zones formed at various extract concentrations. The highest extract concentration produced the largest inhibition zones, with 15.2 mm against Staphylococcus aureus and 13.8 mm against Salmonella typhi. These findings suggest that kepok banana peel extract has potential as a natural antibacterial agent effective against both gram-positive and gram-negative bacteria. This opens the opportunity for utilizing banana peel waste as a plant-based antibacterial alternative.